Keberbaktian Remaja pada Ayah: Pendekatan Indigenous Psychology - Indah Pratiwi; Ivan Muhammad Agung (Jurnal Psikologi Islam dan Budaya, 2022)
This study aims to explore how and why teenagers devoted to their fathers, in terms of gender. The research method used an indigenous psychology approach with the number of research participants were 406 teenagers in the city of Pekanbaru. Participants were asked to answer the question "What behavior do you do to serve your father?”, and “What are your reasons for being devoted to your father?". The results of this study indicate that adolescents who are very devoted to their fathers are shown to behave obediently (43.1%), prosocial (36.2%), respect (11.8%) and responsibility (4.4%). Meanwhile, the reasons why teenagers are devoted to their fathers are because fathers play a role (43.8%), emotional bonds (14.3%), subjective norms (12.1%), blood relations (9.4%), respect (8.9%), and character (7.9%). Teenage boys and girls are devoted to their fathers because the role of fathers is felt by teenagers.